Surface properties of chitin-glucan nanopapers from Agaricus bisporus - Wan Nawawi, Wan Mohd Fazli; Lee, Koon-Yang; Kontturi, Eero; Bismarck, Alexander; Mautner, Andreas (Elsevier B.V., 2020)
The structural component of fungal cell walls comprises of chitin covalently bonded to glucan; this constitutes a native composite material (chitin-glucan, CG) combining the strength of chitin and the toughness of glucan. It has a native nano-fibrous structure in contrast to nanocellulose, for which further nanofibrillation is required. Nanopapers can be manufactured from fungal chitin nanofibrils (FChNFs). FChNF nanopapers are potentially applicable in packaging films, composites, or membranes for water treatment due to their distinct surface properties inherited from the composition of chitin and glucan. Here, chitin-glucan nanofibrils were extracted from common mushroom (Agaricus bisporus) cell walls utilizing a mild isolation procedure to preserve the native quality of the chitin-glucan complex. These extracts were readily disintegrated into nanofibre dimensions by a lowenergy mechanical blending, thus making the extract dispersion directly suitable for nanopaper preparation using a simple vacuum filtration process. Chitin-glucan nanopaper morphology, mechanical, chemical, and surface properties were studied and compared to chitin nanopapers of crustacean (Cancer pagurus) origin. It was found that fungal extract nanopapers had distinct physico-chemical surface properties, being more hydrophobic than crustacean chitin